Pengaruh Risiko ESG Terhadap Kinerja Perusahaan: Efek Moderasi Konsentrasi Kepemilikan - Helmy, Herlina; Susanto, Perengki; Syahrizal, Syahrizal (Jurnal Ecogen, 2025)
This article aims to examine the impact of Environmental, Social, and Governance (ESG) risk on the performance of Indonesian listed companies. We also examined how ownership concentration acts as a moderator between ESG risk and company performance. This paper adopts Morningstar Sustainalytics scores to measure ESG risk and uses Tobin's Q to measure firm performance. Ownership concentration is quantified by the shareholding proportion of the predominant stakeholder. The F-test results demonstrate that the independent variables collectively influence the dependent variable. However, t-test findings demonstrate that ESG risk does not significantly influence firm performance. The MRA test indicates that ownership concentration has no significant impact on the relationship between ESG risk and firm performance.